The administrative culture in education: the case of greece - Λόζγκα Ευαγγελία Χρ.; Στραβάκου Πέλα Αντ. (Education Sciences, 2018)
The following study focuses on Greek administrative culture in education. Although the latter has effects of paramount importance not only on the educational outcomes but also on the workforce, as it can be concluded from the existing literature, the administrative culture has not been put under the spotlight in the Greek educational bibliography. Therefore in this publication, our purpose is to adapt the theoretical framework of administrative culture to educational administrative affairs, and especially in single-person governing bodies, through the systematic review of the literature and from secondary data. We aspire the results of this study to be a basis for further research and we also expect this work to be a theoretical tool both for leaders of the educational system and educational Executives.